2014
DOI: 10.1007/s11356-014-2885-9
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the occurrence of pharmaceuticals in Spanish finished drinking waters

Abstract: Fifty samples of finished drinking waters (FDWs) from Spain covering 12 million inhabitants were tested for 53 pharmaceuticals pertaining to 12 different Anatomical Therapeutic Chemical (ATC) classification system codes. The studied compounds are a combination of most commonly consumed pharmaceuticals with other barely reported in the literature. Five compounds, azithromycin, clarithromycin, erythromycin, sulfamethoxazole, and ibuprofen were tentatively identified by liquid chromatography coupled to tandem mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 94 publications
0
26
0
Order By: Relevance
“…Paracetamol 250 (max) [1] 10000 (max) [2] 154 -634 [3] n.d. -872 [4] Phenazone 950 (max) [5] bql-13 [ 1.9 -3.5 [20] 26-1014 [24] Fenofibrate 9 (max) [6] 1200 (max) [5] n.d. Table SD2. Physicochemical properties of the target pharmaceuticals.…”
Section: Therapeutic Group Compound Concentration (Ng/l) Referencementioning
confidence: 99%
“…Paracetamol 250 (max) [1] 10000 (max) [2] 154 -634 [3] n.d. -872 [4] Phenazone 950 (max) [5] bql-13 [ 1.9 -3.5 [20] 26-1014 [24] Fenofibrate 9 (max) [6] 1200 (max) [5] n.d. Table SD2. Physicochemical properties of the target pharmaceuticals.…”
Section: Therapeutic Group Compound Concentration (Ng/l) Referencementioning
confidence: 99%
“…Recent studies have demonstrated that a combination of the widespread use of pharmaceuticals (PhACs) and their relative inefficient removal in wastewater treatment plants (WWTPs) leads to the detection of low concentrations of these chemicals (sub-ppb levels) in most sewage-impacted aquatic systems [1][2][3][4]. The presence of pharmaceutically active compounds (PhACs) in the receiving waters is concerning as it can represent a threat not only for humans through drinking water intake [5][6] or development of antibiotic-resistant bacteria [7], but also for aquatic organisms [8]. At the same time, chronic and acute toxicity caused by PhACs and other organic micro-contaminants is an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Of 40 pharmaceuticals present in raw sewage, 28 were removed by conventional methods (filtration through a sand bed, chlorination and ozonation). Despite the use of both conventional and advanced treatment methods (including reverse osmosis, considered the most effective), some chemical compounds were still present in treated wastewater: benzoylgonine, iopromide, caffeine, nicotine, cotinine, erythromycin, and paracetamol (38).…”
Section: Pharmaceuticals In Aquatic Environment Fate and Behavior Ementioning
confidence: 99%